Analiza potreb in želja starejših glede uporabe podporne tehnologije v njihovem vsakdanjem življenju - Musil, Bojan (Psihološka obzorja (Ljubljana), 2024)
Ageing brings declining health and associated limitations, affecting the quality of life. Appropriate assistive technology can be crucial in maintaining older people‘s independence in their home living environment. In the present study, we were interested in how older people assess their quality of life, which areas of daily life they find most important, which instrumental activities of daily living they need help with, and whether they would be willing to use new technology for these activities. We were also interested in older people‘s attitudes towards technology and, more specifically, the extent to which they experience fear of using technology. Our survey results show that older people report medium to high levels of all aspects of quality of life, with the highest values recorded for the dimensions „home and neighborhood“ and „psychological and emotional well-being“. In contrast, the lowest mean value is recorded for the dimension „health“. Concerning aspects of fear of technology, aspects of personal failure and preference for human contact are more pronounced than beliefs that new technology is unpleasant to use or useless. Regarding importance, need for help, and willingness to use technology, it can be concluded that the priority areas are health, home care, and mobility. The study‘s findings are essential to guide the design of potential future interventions supported by ICT.
Keywords: ageing; analize potreb; analyses of needs; assistive technologies; kakovost življenja; podporne tehnologije; quality of life; staranje; starejši